2015
DOI: 10.3389/fmicb.2015.00550
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic aromatic hydrocarbons and cytochrome P450 in HIV pathogenesis

Abstract: High prevalence of cigarette smoking in HIV patients is associated with increased HIV pathogenesis and disease progression. While the effect of smoking on the occurrence of lung cancer has been studied extensively, the association between smoking and HIV pathogenesis is poorly studied. We have recently shown the possible role of cytochrome P450 (CYP) in smoking/nicotine-mediated viral replication. In this review, we focus on the potential role of CYP pathway in polycyclic aromatic hydrocarbons (PAH), important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 83 publications
0
21
0
1
Order By: Relevance
“…Exacerbation of viral infection may be related to the fact that AhR activation constrains the type-I interferon response 19 . Other studies have reported that TCDD triggers AhR-dependent HIV-1 gene expression in cell lines, but there has been conflicting data on which HIV-1 promoter elements are responsible (reviewed by Rao and Kumar, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Exacerbation of viral infection may be related to the fact that AhR activation constrains the type-I interferon response 19 . Other studies have reported that TCDD triggers AhR-dependent HIV-1 gene expression in cell lines, but there has been conflicting data on which HIV-1 promoter elements are responsible (reviewed by Rao and Kumar, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, CYP1A-mediated metabolism and activation of PAHs, commonly found in cigarette smoke, has been implicated in development of cancer [ 54 ]. The role of PAHs in enhancing HIV pathogenesis is bolstered by the fact that CYP1 enzyme catalyzed metabolic activation of PAH results in increased production of ROS and oxidative stress [ 55 ]. The CYP1A1 subtype is widely distributed in extrahepatic tissues and its expression is regulated by AHR [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of the 5000 compounds that are present in CSC, polyaryl hydrocarbons (PAHs) are a class of carcinogenic compounds that are implicated by several studies for their potential to induce oxidative stress 10 12 . Benzo(a)pyrene (BaP) is a prototype PAH, which has been widely studied for its carcinogenicity, genotoxicity, and mutagenicity 13 16 .…”
Section: Introductionmentioning
confidence: 99%